Characteristics and Identification of Critical Points of Halal Food at Restaurants in Padang - Faridah, Anni; Holinesti, Rahmi; Syarief, Wirnelis; Mohd Zahari, Mohd Salehuddin (Indonesian Journal of Halal Research, 2022)
Padang is one of the cities in Indonesia with a majority of the Moslem population. It is a crucial thing to be considered by Moslems. This study aims to determine the critical point of halal food found at restaurants in the city of Padang as the novelty of this study. In this study, qualitative methods are used with a population of all restaurants in the city of Padang. The research sources data were informants or restaurant managers by using purposive sampling techniques. The data research was observations and interviews with informants and documentation. Data processing in this study used NVivo 11 software and it is descriptively equipped with data reduction, data presentation, and conclusion making. The result of this research show there are two dominant cooking techniques used in food processing; 65 dishes for frying and 37 dishes for boiling with coconut milk. The food processing using the burned technique, boiled with water, and sautéed are little. There are three types of beverages served; mineral water, sachet drinks (tea, coffee, cappuccino), and fruit processed (fruit juices) as the beverages menu. Identification results show the critical point of halal food in restaurants are divided into four; 1) high water content (beef, chicken, offal, Tempe, and tofu), 2) low water content (salt, sugar, flavoring, sachets, flour, rice flour, paneer flour, and crackers), 3) liquid raw materials (mineral water, cooking oil, soy sauce, and vinegar), and 4) processing equipment (brush polish). Food ingredients and processing equipment that have a critical halal point are meat, crackers, bulk oil, mineral water, and brushes. While other Food Materials, unique packaged ones, already have a halal label on the packaging. This research can contribute in providing information to Moslems about the importance of halal food from all aspects as good as facilitate the restaurant to get halal certification.